Contextual Learning and Its Contribution To The Understanding of Islamic Education - Kusen Kusen; Rahmad Hidayat (AJIS: Academic Journal of Islamic Studies, 2019)
This study aims to develop contextual learning tools for Islamic Education through contextual learning that is valid, practical and effective. The subject of this study was students grade seven Junior High School on odd semester of Rejang Lebong. This research is a development research whose procedure consists of ten steps, namely: (1) problem identification, (2) information collection, (3) product design, (4) design validation, (5) design improvement, (6) product testing , (7) product revisions, (8) usage trials, (9) final product revisions, 10) mass production, so that the syllabus, teaching implementation plan, modules and worksheets are valid, practical and effective. Data collection techniques are carried out by observation, questionnaire, and test results. The data collected was analyzed by percentage. The results of this study are: syllabus, teaching implementation plan, modules and Student Worksheets that have been validated by the validator are valid. Then based on the response of students to the module and student worksheet grade seven Islamic Education in Rejang Lebong is practical. then the teaching implementation plan, modules and Student Worksheets provided in the learning process are effective.